Variation of atmospheric volatile organic compounds over the Southern Indian Ocean (30–49°S) - Colomb, Aurélie; Gros, Valérie; Alvain, Séverine; Sarda-Esteve, R.; Bonsang, B.; Moulin, C.; Klüpfel, T.; Williams, J. (Environmental Chemistry, 2009)
International audience Considering its size and potential importance, the ocean is poorly characterised in terms of volatile organic compounds (VOC) that play important roles in global atmospheric chemistry. In order to better understand their potential sources and sinks over the Southern Indian Austral Ocean, shipborne measurements of selected species were made during the MANCHOT campaign during December 2004, on board the research vessel Marion Dufresne. Along the transect La Réunion to Kerguelen Island, air measurements of selected VOC (including dimethylsulfide (DMS) isoprene, carbonyls and organohalogens), carbon monoxide and ozone were performed, crossing subtropical, temperate and sub-Antarctic waters as well as pronounced subtropical and sub-Antarctic oceanic fronts. The remote marine boundary layer was characterised at latitudes 45-50°S. Oceanic fronts were associated with enhanced chlorophyll and biological activity in the seawater and elevated DMS and organohalogens in the atmosphere. These were compared with a satellite-derived phytoplankton distribution (PHYSAT). Diurnal variation for isoprene, terpenes, acetone and acetaldehyde was observed, analogously to recent results observed in mesocosm experiments.